Umbilicus-sparing laparoscopic versus open approach for treating symptomatic urachal remnants in adults - Liu, Zheng (Medicine (Baltimore), 2018)
The traditional surgical approach for removing a symptomatic urachal remnant is via a lower midline laparotomy and infraumbilical incision or a laparoscopic approach with umbilicoplasty. We reviewed our experience with umbilicus-sparing laparoscopic urachal remnant excision in a single-center study and evaluated its efficacy versus open approach (OA). This study was a retrospective study. Between March 2012 and September 2016, 32 consecutive patients with symptomatic urachal remnants underwent the umbilicus-sparing laparoscopic approach (USLA) (n = 17) or OA (n = 15). The efficacy, recovery, and long-term outcomes were reviewed. Our Results showed that the clinical characteristics of the patients in each group, such as age, gender, body mass index (BMI), and disease type, had no significant differences (P > .05). No significant difference was found in the surgical procedure times (76.1 ± 15.4 vs 69.2 ± 13.9 minutes, P = .189) and intraoperative blood loss (29.4 ± 13.3 vs 32.2 ± 12.9 mL, P = .543) between the USLA groups and OA groups. However, the mean postoperative hospital stay (patients with bladder cuff excision: 4.1 ± 1.8 vs 6.1 ± 1.4 days, P = .040 and patients without bladder cuff excision: 1.8 ± 0.5 vs 3.6 ± 0.8 days, P < .001) and the time of full recovery (11.2 ± 1.9 vs 15.6 ± 3.1 days, P < .001), the USLA group were both significantly shorter than that of the OA group. No infected recurrence and malignant transformation had occurred at a mean follow-up of 32.4 ± 8.1 and 34.1 ± 8.8 months in USLA group and OA group, respectively. In conclusion, to minimize the morbidity of radical excision, umbilicus-sparing management of benign urachal remnants in adults is a safe and efficacious alternative with superior cosmetic outcomes, postoperative recovery compared with an OA or umbilicoplasty.